PENTINGNYA METODE PEMBELAJARAN BAGI PENINGKATAN MINAT BELAJAR MAHASISWA PROGRAM STUDI SARJANA PENDIDIKAN AGAMA KRISTEN SEKOLAH TINGGI TEOLOGI DUTA PANISAL JEMBER - Fitra Syukur Iman Zai; Yehezkiel Sugeng Mulyono (Sekolah Tinggi Teologi Duta Panisal, 2022)
The research in this thesis is motivated by several problems experienced by the Duta Panisal Theological College Students, especially in the teaching and learning process in the classroom. The learning process is essentially a process in which there is interaction between educators and students, both direct and indirect interactions. In the process of this interaction, of course, there are differences between educators and students. By looking at these different interaction processes, an educator must have expertise in creating student interest in learning, a comfortable classroom atmosphere and being able to make students active in the learning process. This will be realized if educators have good and appropriate strategies, one of which is by utilizing learning methods. The selection and use of appropriate learning methods will make it easier for an educator to deliver learning materials and produce effective and efficient learning. This study uses a qualitative method with a case study approach. The research findings in this thesis can be trusted for the validity of the data because they have gone through a scientific research process. Based on the results of triangulation, the researchers found several findings based on the results of interviews and existing data, one of which was the difference of opinion expressed by the STT Duta Panisal lecturer and the STT Duta Panisal students on the learning method that influenced the increase in interest in learning.